Herbert Samuel Heelas Macaulay(1864-1946) - Winclair,J.E.Asunwontan (Evans Brothers (Nigeria Publishers) Ltd, 2008)
Herbert Macaulay is one of the collection in the People who make our History series. The assortment is a range of short story books about the heroic deeds of notable people worthy of emulation both in the past and present.
Keywords: Autobiography; Biography; Non-Fiction